Marketing Strategy Of JKT48 As A Japanese-Style Idol Group In Attracting New Markets In Indonesia - Setiawan, Albert Octavio; Chrisdina (Institut Komunikasi dan Bisnis LSPR, 2023)
The world of performances is very developed in Indonesia, one of which is in the country's music industry. Pop music or songs are songs that are often heard by Indonesian people, due to the influence of outside culture, one of which is Japanese culture, so in Indonesia, there are J-pop style songs or Japanese-style songs. But persistence in Indonesia is not as popular as K-Pop. One of the well-known J-Pop in Indonesia has survived until now, namely JKT48 which has been established since 2012. JKT48 is an idol group branch of AKB48 which was formed for the first time in Japan, specifically in the city of Akihabara. This study uses a qualitative methodology and also Hovland's persuasive theory wants to see the existence of J-pop, especially JKT48, to survive with the support of its fans and attract new fans. And the researchers interviewed 1 person from JKT48 marketing as well as their new fans and judged that JKT48's marketing is unique, making JKT48 still exist in the community and survive to this day.